Driver behaviour analysis through simulation - Gregoriades, Andreas; Florides, Christos; Lesta, Vicky Papadopoulou; Pampaka, Maria (My University, 2013)
Human error is one of the principal influencing factors that lead to road accidents, and is attributed to increased mental workload induced by distractions such as advertisements and in-vehicle music. Workload, however, is characterized by intrinsic properties and hence difficult to be observed and quantified. Phenotype behaviours, such as lateral deviations, speed and headway, act as good indicators of driver workload and driving style. Driving simulators emerged as a promising technology for the analysis of driving conditions and road users' behaviour in an attempt to tackle the problem of road accidents. However, the cost of designing or owning a simulator to conduct a safety analysis is prohibitive for many government agencies. The work presented herein demonstrates the design and development of a driving simulator, using a 3D game engine. The simulator was employed to analyze the driving behaviours of local road users for a chosen black spot in Nicosia-Cyprus. Data collected from the experiments were analyzed and preliminary results are presented along with conclusions. © 2013 IEEE.